Los malos tratos a la infancia: juristas reformadores y el debate sobre la patria potestad en el Código Civil español (1889-1936) - Santos Sacristán, Marta (Cuadernos de Historia Contemporánea, 2002)
This paper is centred in the paternal authority that supposed, in Spain, an obstacle to protect children and girls of the child abused that suffered. The speech is analyzed generated by jurists and socials reformers who coincided in denouncing the inability of the tribunals to pursue the abuses and they demanded, for this reason, the reformation of the civil Code and the penal Code.